PENGARUH KOMPOS ISI RUMEN SAPI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG HIJAU (Vigna radiata L.) - Novita Heci Lestari; Murniati Murniati; Armaini Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to know the effect of composted contains cow rumen and get a dose of composted cow rumen content best to the growth and yield of mung bean. This research land conducted in UPT area of research Farm in Faculty of Agriculture, Riau University from January to March 2016. This research used a completely randomized design (CRD), which consists of 6 treatments: K0: Without composted cow rumen contents, K1 : 10 ton/ha, K2: 20 ton/ha, K3: 30 ton/ha, K4: 40 ton/ha, K5: 50 ton/ha. Parameters measured were plant height, number of primary branch, flowering time, harvesting time, pods number per plant, the percentage of pithy pods number per plant, weight of 100 seeds and production per plot. The results of the research giving composting cow rumen content dose 20 ton/ha able to optimize growth and production of mung bean.Keywords: Compost, cow rumen contents, Mung bean, growth and yield